Spangled perch (Leiopotherapon unicolor) in the southern Murray‐Darling Basin: Flood dispersal and short‐term persistence outside its core range. (6th February 2015) - Ellis, Iain; Whiterod, Nick; Linklater, Danielle; Bogenhuber, Deborah; Brown, Paul; Gilligan, Dean
Abstract The spangled perch Leiopotherapon unicolor is considered a rare vagrant in the southern Murray‐Darling Basin, Australia, due to its intolerance of the relatively cool water temperatures that prevail during winter months. This study details 1342 records of the species from 68 locations between 2010 and 2014 outside its accepted 'core adult range' following widespread flooding during 2010 and 2011. Although records of the species declined over 2013, L. unicolor remained resident in the southern Murray‐Darling Basin as of April 2014. The species persisted in several locations for three consecutive winters with recruitment documented at two sites. This study represents the first identification of the dispersal of large numbers of L. unicolor into the southern Murray‐Darling Basin, persistence beyond a single winter, and recruitment by the species in habitats south of its recognized 'core adult range'. Targeted research would determine the potential for predicted environmental changes (artificially warmer drainage wetlands, climate change and greater floodplain connectivity) to facilitate longer term persistence and range expansion by the species in the southern Murray‐Darling Basin.